In Search of Respect: Examining Arrestee Satisfaction with Police - Myrstol, Brad A. (American journal of criminal justice, 2011)
Recent research suggests that attitudes toward police hinge upon the procedures officers use in their interactions with the public. Using survey data collected from a sample of adults arrested and booked into a local jail in Washington County, Arkansas, this paper examines some of the factors that influence arrestees’ satisfaction with police. Results reveal that the most important factor influencing arrestees’ opinions of police was their belief in the benevolence of police actions, followed by their perceptions of the effectiveness of police, whether or not their arresting officer treated them with respect, racial group membership, and total household income. These findings lend support to the “normative” or “process-based” model of policing. The authors discuss the implications of these findings for police and jail administrators.